2021
DOI: 10.1136/ijgc-2021-002806
|View full text |Cite
|
Sign up to set email alerts
|

Impact of hypoxia on cervical cancer outcomes

Abstract: The annual global incidence of cervical cancer is approximately 604 000 cases/342 000 deaths, making it the fourth most common cancer in women. Cervical cancer is a major healthcare problem in low and middle income countries where 85% of new cases and deaths occur. Secondary prevention measures have reduced incidence and mortality in developed countries over the past 30 years, but cervical cancer remains a major cause of cancer deaths in women. For women who present with Fédération Internationale de Gynécologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 102 publications
0
18
0
Order By: Relevance
“…gov website. [7][8][9] All of these studies have corresponding conference abstracts included in the final search results. [10][11][12]…”
Section: Resultsmentioning
confidence: 99%
“…gov website. [7][8][9] All of these studies have corresponding conference abstracts included in the final search results. [10][11][12]…”
Section: Resultsmentioning
confidence: 99%
“…Extrinsic abnormalities of tumor microenvironment, particularly tumor hypoxia, reduce the efficacy of radiotherapy, shorten survival time, and increase recurrences [ 5 ]. A recent review article summarized hypoxia-targeted strategies and identified further research and new treatment paradigms needed to improve patient outcomes [ 6 ]. Hypoxia-inducible factor (HIF) is a transcriptional activator of various genes related to cellular adaptive responses to hypoxia.…”
Section: Introductionmentioning
confidence: 99%
“…In 2018, there were about 569,000 confirmed cases of CC and about 311,000 deaths worldwide (1). Approximately 85% of de aths from CC occur in underdeveloped countries and areas (2), with the highest mortality rates found in parts of America and sub-Saharan Africa (3).…”
Section: Introductionmentioning
confidence: 99%